2010
DOI: 10.1111/j.1872-034x.2010.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of patients with autoimmune hepatitis seropositive for anticentromere antibody

Abstract: These results suggest that the emergence of ACA is not a distinct entity of AIH, despite its clinical characteristics of a significantly higher frequency of concurrent autoimmune diseases and lower serum IgG levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…The reported patients are all middle-aged women with certain autoantibodies and hypergammaglobulinemia. Himoto et al reported that AIH patients with anticentromere antibodies have relatively low gamma-globulin levels (12), consistent with that observed in our case.…”
Section: Discussionsupporting
confidence: 92%
“…The reported patients are all middle-aged women with certain autoantibodies and hypergammaglobulinemia. Himoto et al reported that AIH patients with anticentromere antibodies have relatively low gamma-globulin levels (12), consistent with that observed in our case.…”
Section: Discussionsupporting
confidence: 92%
“…Anti-smooth muscle antibodies are directed mostly to the polymerized form of actin and are traditionally associated with type 1 autoimmune hepatitis, but they can also be observed in a small fraction of HCV patients, usually at a lower titer than in autoimmune hepatitis [16]. HCV patients presenting anti-smooth muscle autoantibodies appear not to differ from those without these autoantibodies concerning clinical profile and response to treatment [15], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our patient had type 2 diabetes mellitus. No significant differences in age, sex, and onset pattern of the disease, progression to hepatic failure, and relapse rate were present between ACA-AIH and other AIH groups [ 7 ].…”
Section: Discussionmentioning
confidence: 99%